Study on the effect of humidity on coal mine dust concentration monitoring and its compensation strategy - ZHANG Anran (Gong-kuang zidonghua)
The humidity in mines significantly affects the monitoring quality of coal mine dust concentration. This study aims to improve the precision of dust concentration monitoring in high-humidity underground coal mine conditions, through investigating the influence of humidity on dust concentration monitoring and exploring humidity compensation techniques. Based on the observations of the hygroscopic growth and morphology of coal mine dust particles, experiments were conducted to obtain the variation pattern of coal mine dust particle size under different humidity conditions and to reveal the mechanism by which humidity affects dust concentration monitoring. The particle size of coal mine dust increased exponentially with rising humidity. When environmental humidity increased gradually from 50% to 90%, the coal mine dust concentration exhibited an exponential growth trend. To address this, an online humidity compensation technique based on light-scattering characteristics with multiple angles was proposed. The relationships among environmental humidity, dust particle size, and scattered light flux were investigated. A humidity compensation experimental model was developed and integrated into a light-scattering dust concentration monitoring unit with multiple angles. In this way, humidity compensated coal mine dust concentration monitoring was achieved. Results showed that the monitoring error of the humidity-compensated multi-angle light-scattering unit was ≤11.2%, a 2.9% reduction compared to the uncompensated unit, confirming the effectiveness of the compensation method.